Information technology. International standardized profile RB. Relaying the connection-mode network service. Definition of profile RB51.1121, relaying the connection-mode network service between CSMA/CD LAN subnetworks and PSDNs using virtual calls over a digital data circuit/CSDN leased line permanent access Part 5, (15th November 1998) - British Standards Institution,
No abstract available